Pengaruh Lama Pengeringan Terhadap Karakteristik Organoleptik Teh Herbal Kulit Pala (Myristica fragrans Houtt.) - Palijama, Syane (Jurnal Teknologi Pangan dan Industri Perkebunan (LIPIDA), 2024)
The aim of this research was to determine the appropriate drying time for the organoleptic characteristics of nutmeg peels herbal tea. This research used a completely randomized design with 4 levels of drying time treatment, namely: T1 = 3 hours, T2 = 6 hours, T3 = 9 hours, T4 = 12 hours, and repeated 3 times. The results of the research showed that the 12 hour drying treatment with organoleptic characteristics, both hedonic test and hedonic quality test, respectively, included: color with a scale value of 4.45 (like) and 4.19 (brownish yellow), taste with a scale value of 4.49 ( like) and 4.82 (very nutmeg-tasted) and overall acceptance of 4.68 (very like). The drying time of 3 hours has an effect on the flavour of nutmeg peels herbal tea with an assessment score of 4.08 (like it) and 4.67 (very nutmeg-flavored).